Lower Rates of Emergency Department Visits and Hospitalizations Among Patients With Chronic Hepatitis C With Sustained Virological Response to Interferon-Free Direct-Acting Antiviral Therapy (2014–2018) . (11th February 2022) - Gordon, Stuart C; Teshale, Eyasu H; Spradling, Philip R; Moorman, Anne C; Boscarino, Joseph A; Schmidt, Mark A; Daida, Yihe G; Rupp, Loralee B; Trudeau, Sheri; Zhang, Jiaqi; Lu, Mei; ,
Abstract: We compared rates of emergency department visits and hospitalizations between patients with hepatitis C virus who achieved sustained virological response after direct-acting antiviral therapy (case patients) and matched controls. Among 3049 pairs, case patients demonstrated lower rates of liver-related emergency department visits ( P =  .01) than controls; all-cause and liver-related hospitalization rates and number of hospitalized days were also lower in case patients ( P < . 001).